Sample size estimation: Current practice and considerations for original investigations in MRI technical development studies - Hanspach, Jannis; Nagel, Armin Michael; Hensel, Bernhard; Uder, Michael; Koros, Leon; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2020)
Purpose: To investigate and to provide guidance for sample size selection based on the current practice in MR technical development studies in which healthy volunteers are examined. Methods: All original articles published in Magnetic Resonance in Medicine between 2017 and 2019 were investigated and categorized according to technique, anatomical region, and magnetic field strength. The number of examined healthy volunteers (ie, the sample size) was collected and evaluated, whereas the number of patients was not considered. Papers solely measuring patients, animals, phantoms, specimens, or studies using existing data, for example, from an open databank, or consisting only of theoretical work or simulations were excluded. Results: The median sample size of the 882 included studies was 6. There were some peaks in the sample size distribution (eg, 1, 5, and 10). In 49.9%, 82.1%, and 95.6% of the studies, the sample size was smaller or equal to 5, 10, and 20, respectively. Conclusion: We observed a large variance in sample sizes reflecting the variety of studies published in Magnetic Resonance in Medicine. Therefore, it can be concluded that it is current practice to balance the need for statistical power with the demand to minimize experiments involving healthy humans, often by choosing small sample sizes between 1 and 10. Naturally, this observation does not release an investigator from ensuring that sufficient data are acquired to reach statistical conclusions.
CRIS-Team Scopus Importer:2020-10-23
Keywords: current practice; methodological MRI developments; number of subjects; number of volunteers; proof-of-principle studies; sample size estimation